Analisis Implementasi Kebijakan Akuntansi Pendapatan Pada Pemerintah Kota Malang - San rudiyanto; Mirza Dyah Ariyanti (Program Pendidikan Vokasi Universitas Brawijaya, 2018)
This study aims to analyze the implementation of income accrual-based accounting policies in Malang City Government. This research is a qualitative research by using descriptive approach. Sources were obtained from unstructured interviews, observations, and documentation studies. The results of research related to the implementation of accounting policy in Malang City Government can be summarized as follows, namely the implementation of accounting policy of local tax revenue in general has been referring and in accordance with Government Regulation number 71 of 2010 on Accrual Based Government Accounting Standards. In fact, the City Government of Malang also has owned and established rules of technical implementation related to the System and Accounting Policies in the mayoral regulations. However, there is still a mistake in the recognition and recording of receipts obtained from the overpayment of local taxes. The city government of Malang noted the overpayment of this area tax as other income. This is not in accordance with the principle of revenue accounting in accordance with applicable SAP.